Restoration of normal colonic motor patterns and meal responses after distal colorectal resection. Issue 4 (18th January 2016) - Vather, R.; O'Grady, G.; Arkwright, J. W.; Rowbotham, D. S.; Cheng, L. K.; Dinning, P. G.; Bissett, I. P.
Abstract : Background: Colorectal resections alter colonic motility, including disruption of control by neural or bioelectrical cell networks. The long‐term impact of surgical resections and anastomoses on colonic motor patterns has, however, never been assessed accurately. Fibreoptic high‐resolution colonic manometry was employed to define motility in patients who had undergone distal colorectal resection. Methods: Recruited patients had undergone distal colorectal resections more than 12 months previously, and had normal bowel function. Manometry was performed in the distal colon (36 sensors; 1‐cm intervals), with 2‐h recordings taken before and after a meal, with comparison to controls. Analysis quantified all propagating events and frequencies (cyclical, short single, and long single motor patterns), including across anastomoses. Results: Fifteen patients and 12 controls were recruited into the study. Coordinated propagating events directly traversed the healed anastomoses in nine of 12 patients with available data, including antegrade and retrograde cyclical, short single and long single patterns. Dominant frequencies in the distal colon were similar in patients and controls (2–3 cycles/min) (antegrade P = 0·482; retrograde P = 0·178). Compared with values before the meal, the mean(s.d.) number of dominant cyclical retrograde motor patterns increased in patients after the meal (2·1(2·7) versus 32·6(31·8) in 2 h respectively; P < 0·001), similar to controls ( P = 0·178), although the extent of propagation was 41 per cent shorter in patients, by a mean of 3·4 cm ( P = 0·003). Short and long single propagating motor patterns were comparable between groups in terms of frequency, velocity, extent and amplitude. Conclusion: Motility patterns and meal responses are restored after distal colorectal resection in patients with normal bowel function. Coordinated propagation across healed anastomoses may indicate regeneration of underlying cellular networks. Abstract : Normal motor patterns restored across anastomoses